STUDI PEMANFAATAN SIFAT PEMBIASAN CAHAYA PADA PORTABLE BRIX METER UNTUK MENGANALISIS HUBUNGAN KONSENTRASI LARUTAN SUKROSA (C12H22O11) TERHADAP pH - Iva Nistiyanti; Eko Hidayanto (Youngster Physics Journal, 2015)
Sucrose concentration was analyzed using portable brix meter to show the acidity and alkalinity. Materials the brix were sucrose, honey, milk, and vinegar. Sucrose solution was diluted with aquades at concentration of 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, while concentration solution of milk, honey, and vinegar at 5%, 10%, 15% ,20%, 25%, 30%, 35%, 40%, 45%. Solution at each concentration was measured by Portable Brix Meters to determine the concentration of sucrose with work on the principle of light refraction. The acidity or alkalinity of each solution was measured by a pH meter, so we get the graph calculation and the relationship between the concentration of sucrose solution pH to change the acidity or alkalinity of a solution. Increased concentration on pure sugar or sucrose, causing increased levels of alkalinity, while the honey, milk, and vinegar, with increased concentrations cause acidity. Data were analyzed with logarithmic graph approach. The correlation between the concentration of sucrose solution C with a pH in pure sucrose solution  with R2=0.913. The correlation between the concentration of sucrose solution C with a pH in solution of honey, milk, and vinegar.  with R2 = 0.792, dengan R2= 0.956,  with R2= 0.407,  with R2 = 0.974,  with R2= 0.983. The difference of pH value and concentrations are very small. Keywords: sucrose solution, concentration, pH meter, portable Brix meter